Del biocentrismo a la seguridad humana: un enfoque en el marco del reconocimiento del páramo de Pisba como sujeto de derechos (2020)
This paper discusses the status of mining operations vis-a-vis nature as a subject of rights to the extent that they represent a serious threat not only to the fauna and flora in the areas where mining takes place but also to the human being. The legal system has advanced in this regard by prohibiting mining in national and regional natural parks, forest reserves, and paramo zones. The high courts have also contributed to protecting and preserving nature as is the case of the Pisba Paramo, which they recognize as a subject of rights. In addition to this background, the environmental conflict is methodologically characterized to identify and define it. Its location, social aspects, and how it was resolved are explained to demonstrate that the theory of biocentrism has been adopted in court decisions aimed at ensuring the protection of nature.